Development of a dual-target RAA-LFD assay for point-of-care and visual detection of Salmonella pullorum and Salmonella typhimurium in fecal samples - Zuo, Weiye; Shao, Congxue; Qin, He; Gao, Hongwei; Sun, Xuemei; Wang, Pengyan; Ren, Jingjing (Frontiers in Veterinary Science, 2025)
To address the need for rapid detection of Salmonella pullorum (S. pullorum) and Salmonella typhimurium (S. typhimurium) in the poultry industry, we developed a dual-target point-of-care system integrating recombinase-aided amplification (RAA) with lateral flow dipsticks (LFD) for visual pathogen identification (RAA-LFD). Using primers and probes specifically targeting the ipaj gene of S. pullorum and the STM4497 gene of S. typhimurium, the optimized assay achieved detection at 37 °C within 20 min. The dual RAA-LFD assay showed exceptional specificity with no cross-reactivity toward non-target pathogens. Detection sensitivities reached 5.91 × 101 CFU/mL (S. typhimurium) and 2.37 × 102 CFU/mL (S. pullorum) in pure cultures. In contrast, genomic DNA detection achieved identical limits of 5.70 × 101 fg/μL (S. typhimurium) and 4.53 × 101 fg/μL (S. pullorum). In artificially contaminated samples, the detection limits reached 3.92 × 102 CFU/mL for S. pullorum and 6.26 × 101 CFU/mL for S. typhimurium. Clinical validation demonstrated 96.88–100% coincidence with biochemical identification and multiplex PCR results. This study confirms the precision and high sensitivity of the dual RAA-LFD assay as a detection methodology. Furthermore, by eliminating reliance on complex traditional techniques, this technology provides an efficient grassroots-level field screening tool with significant potential for preventing avian salmonellosis and enhancing food safety monitoring.